Form and Meaning of Mosque Naming in Mataram City: Morphosemantic Study - Ilham Ramadhani; Burhanuddin; Ratna Yulida Ashriany (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2023)
Research on the Form and Meaning of Mosque Naming in Mataram City: This Morphosemantic Study aims to describe the form of mosque names morphologically and examine their meaning semantically. This research is a type of research with a descriptive qualitative approach. The data in this research are the names of mosques in Mataram City, while the data sources in this research include mosque administrators, the public, articles and other media. The data collection method in this research uses the Listening method with advanced techniques, the Listening Involvement Cakap technique, the Free Listening Involvement Cakap technique, the Note taking technique and the Recording technique. Apart from that, the Listening method is strengthened by the Interview method with the Cakap Semuka advanced technique. Furthermore, it is also strengthened by the Documentation method. The data analysis methods used include the Intralingual Matching method, the Extra Lingual Matching method and the Distributional method. The method for presenting data analysis in this research uses informal methods. The results of this research include the morphological forms of mosque names which are classified into words and phrases. Based on their meaning, mosque names are divided into lexical meaning and contextual (socio-cultural) meaning.